Pengaruh Khatam Al-Qur’an dan Bimbingan Guru terhadap Kemampuan Membaca Al-Qur’an di MTS Nurul Ihsan Cibinong Bogor - Abdullah Syafei; Nanat Fatah Natsir; Mohamad Jaenudin (Jurnal Dirosah Islamiyah, 2020)
ABSTRACT This study aims to analyze the influence of teacher guidance and the Qur'anic khatam on the ability to read the Qur'an at MTS Nurul Ihsan Cibinong. The research method used is a descriptive qualitative research method. The result was that the majority (60.3%) of MTS students Nurul Ihsan Cibinong, Bogor, met the Al-Qur'an's Khatam target with very good criteria. The rest, including both (18.0%) and moderate (9.8%). There is a moderate correlation between Khatam Al-Qur'an and Ability to Read the Qur'an at MTs Nurul Ihsan Bogor. This is evidenced by the correlation number or R2 of 0.575. That is, the variables of khatam and guidance can explain the ability to read the Qur'an by 57.5%. The rest is explained by other variables not examined. Keywords: Al-Qur'an, guidance, khatam, reading, students